Implementation of a Wireless Sensor Network with Mesh Topology with XBee for Centralized Building Room Monitoring - Hutabarat, Nicodemus; Siraita, Regina Sirait; Junaidi, Junaidi; Pardede, Morlan (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Room monitoring in office buildings or campuses such as POLMED, especially the use of lights and indoor activities after working hours, is very necessary. In this research, a wireless sensor network with a mesh topology was implemented. A network with a mesh topology allows each node to establish communication with surrounding nodes and send information through intermediary nodes. This implementation is able to provide benefits by increasing the network area, number of sensor nodes and network reliability. The monitoring system is designed to consist of sensor nodes and server nodes. Each server node consists of a light sensor, motion sensor and XBee RF module for communication placed in each room, so that each node can communicate and send information to the monitoring center. The server node as a monitoring center receives data from sensor nodes which can be displayed in room mapping. In testing the sensor node network, it can successfully send a message to the server node if there is at least one intermediate node that can forward the message to the destination. From the test results, it was found that sending one frame with 17 bytes was 0.09 s, 0.11 s, and 0.12 s for 1 hop, 2 hops and 3 hops respectively.